OPTIMIZATION OF POWER CONTROL TO ENSURE STABLE ELECTRICITY SUPPLY IN MICRO-HYDRO POWER PLANT - Nota Effiandi; Rahmat Hafiz; Mutiara Efendi; Vamellia Sari Indah Negara; Reodhy Hamzah (Bajang Institute, 2025)
A This study proposes an optimization-based power control strategy to enhance voltage and frequency stability in micro-hydro power plants (MHPP). The approach integrates multi-objective optimization, adaptive control, predictive algorithms, and robust mechanisms to overcome instability caused by load and water flow variations. System modeling and simulation were performed in MATLAB/Simulink, followed by experimental validation on a laboratory-scale prototype. Results show significant improvements compared to conventional PID and fixed-gain Electronic Load Controllers (ELC), reducing voltage and frequency deviations by up to 69% and 67%, respectively. Total Harmonic Distortion (THD) decreased to 3.8%, power factor improved to 0.93, and overall efficiency reached 87.2%. The method proved effective, stable, and feasible for real-time microcontroller implementation, offering a reliable solution for isolated and rural MHPP systems.